Human Anatomy Self-Assessment Review Questions - Nolan, Michael F.; McNamara, John P. (Open textbook library., 2022)
Human anatomy is one of the foundational disciplines in the training of health care professionals. Knowledge of human structure at both the macroscopic and microscopic levels serves as a framework for the study of normal function and dysfunction. This workbook presents a series of questions related to a particular area of anatomy. Answers to those questions are included at the end of the book. This approach to self-assessment in basic human anatomy will be helpful to students in preparing for clinical-based learning activities as well as for other types of knowledge assessment and evaluation.